Molecular epidemiology, antimicrobial susceptibility, and characterization of fluoroquinolone non-susceptible Streptococcus pyogenes in Japan - Tatara, Kazuaki; Gotoh, Kenji; Okumiya, Kiyohito; Teramachi, Mariko; Ishimoto, Kazuhisa; Tanaka, Yuhei; Iwahashi, Jun; Shindou, Shizuo; Yamashita, Yushiro; Watanabe, Hiroshi (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2020)
Streptococcus pyogenes (Group A streptococci: GAS) are known to cause a wide variety of human illnesses, some of which can be life-threatening. Usually, penicillin is the first-choice agent for the treatment of GAS infections. For patients with penicillin or beta-lactam antibiotics allergies, macrolide drugs are recommended as an alternative therapy. However, an increased prevalence of macrolide-resistant GAS (MRGAS) has been reported in many countries. Furthermore, fluoroquinolone non-susceptible GAS has been reported. The present study was focused on determining the features of fluoroquinolone non-susceptible strains collected from children with pharyngotonsillitis in the southwestern areas of Japan. To reveal the characteristics of fluoroquinolone non-susceptible GAS, we investigated the MIC, T-serotype, emm typing, and PFGE of 298 GAS strains isolated in the Fukuoka southwest area of Japan between 2011 and 2013. We determined that fluoroquinolone non-susceptibility shows a MIC to tosufloxacin of ≧1 μg/ml. We identified 33 (11.1%) fluoroquinolone non-susceptible GAS strains. In these strains, 6 T-serotypes and 9 emm/MLST patterns were detected. The predominant combinations were emm6/ST382 (14 strains, 42.4%) and emm89/ST101 (5 strains, 15.2%). PFGE classified 10 pulsotypes, and each was quite different. These results showed that fluoroquinolone non-susceptible GAS strains have a variety of origins. The usage of fluoroquinolone drugs could have a negative effect on the antimicrobial drug sensitivity of GAS in Japan. Considering such a situation, continuous monitoring of quinolone non-susceptible GAS is necessary.